Association of Body Roundness Index and A Body Shape Index with Obstructive Sleep Apnea: insights from NHANES 2015–2018 data - Pan, Xue; Liu, Fang; Fan, Jiayi; Guo, Qihan; Guo, Mengfei; Chen, Yuxin; Sun, Jingyao; Cao, Xuezhao (Frontiers in Nutrition, 2024)
Objective: This study examines the relationship between several anthropometric indices-Body Roundness Index (BRI), A Body Shape Index (ABSI), Waist-to-Weight Index (WWI), Waist Circumference (WC), and Body Mass Index (BMI)-and the prevalence of Obstructive Sleep Apnea (OSA) using data from the National Health and Nutrition Examination Survey (NHANES) spanning 2015 to 2018.Methods: A retrospective cross-sectional analysis of 7,004 adult participants was conducted using NHANES 2015-2018 data. Multivariable-adjusted logistic regression models were employed to assess the association between BRI, ABSI, and OSA. Non-linear relationships were explored via smooth curve fitting and threshold effect analysis using a two-part linear regression model. Subgroup analyses identified sensitive populations, and the discriminatory power of the indices in screening OSA was assessed using Receiver Operating Characteristic (ROC) curves.The analysis revealed a significant positive association between BRI and OSA, with a threshold effect observed at a BRI of 4.3. Below this threshold, OSA risk increased with higher BRI; however, no significant association was found above this threshold. Similarly, ABSI demonstrated a threshold effect at 8.2, with OSA risk positively associated to the left and negatively associated to the right. Subgroup analyses indicated stronger associations in younger and non-diabetic populations.ROC analysis identified BRI as a promising predictive tool for OSA, with an AUC of 0.64 (95% CI: 0.62-0.65).Conclusion: BRI demonstrates significant potential as a predictive index for OSA incidence, warranting further large-scale prospective studies to validate these findings.